Effect of Talc on Thermal and Mechanical Properties of Poly(L-lactic acid) - Cai, Yan-Hua (Asian Journal of Chemistry, 2013)
The thermal and mechanical properties of poly(L-lactic acid)/talc composites with different content of talc has been investigated. Non-isothermal crystallization shows that talc can serve as a nucleating agent for the crystallization and increase the overall crystallization rate of poly(L-lactic acid). The scanning electron microscope shows that the addition of talc results in substantially increasing of nucleating density. Thermogravimetric analysis shows that the onset degradation temperature of poly(L-lactic acid)/talc composites significantly decreases. Talc can makes the tensile strength and modulus of poly(L-lactic acid)/talc composites enhance, however, the elongations at break of poly(L-lactic acid)/talc composites steadily decreases with increasing of talc.